(untitled) (New Jersey, 2006)
Pankaj Ghemawat, in collaboration with Bruno Cassiman, David Collis and Jan Rivkin, has prepared the second edition of an introductory strategy textbook that adopts a value-focused, firm-centered perspective on strategy. The book is meant to be rigorous in its research base, pragmatic in its focus, and concise. The second edition includes new, full-length chapters on competitive dynamics (with Bruno Cassiman) and on corporate strategy (with Jan Rivkin).
Keywords: Strategic planning,Industrial management,Competition